Influence of surface texturing and coatings on mechanical properties and integration with bone tissue: an in silico study - Alshadidi, Abdulkhaliq Ali F.; Dommeti, Vamsi Krishna; Aldosari, Lujain Ibrahim N.; Hassan, Saeed Awod Bin; Okshah, Abdulmajeed; Merdji, Ali; Roy, Sandipan (Frontiers in Bioengineering and Biotechnology, 2024)
This investigation delves into the mechanical behaviour of titanium dental implants, a preferred choice for tooth replacement due to their superior reliability over alternative materials. The phenomenon of implant loosening, frequently induced by masticatory activities, underscores the significance of surface modification or texturing to bolster the interaction between the implant and bone tissue. This research comprehensively examines the effects of four distinct surface texturing techniques and five varied bone quality conditions on the biomechanical performance of these implants. The scope of this study is delineated by its focus on implants of diameters 4 mm and 6 mm, with lengths measuring 9 mm and 12 mm respectively. Furthermore, the analysis incorporates the evaluation of four different coatingshydroxyapatite, HA3TO, HA3Sr, and HA1.5TO1.5Sr-to investigate their efficacy in enhancing the osseointegration process on textured surfaces of dental implants. The experimental design entails the assessment of stress distribution within the implant and its coatings, alongside the strain exerted on the surrounding cancellous bone, under the conditions of an average vertical biting force. A comparative analysis between implants with solid and those subjected to surface texturing techniques has been conducted. This comparison elucidates the advantageous microstrain profiles presented by certain textured surfaces, which are deemed more conducive to optimal osseointegration. Notably, across all examined textures, the application of hydroxyapatite (HA) and a modified HA composition (HA1.5TO1.5Sr) demonstrates significant improvements in mechanical stability, particularly in scenarios involving weak and very weak bone conditions. This study's findings contribute to the ongoing advancement in dental implant technology, emphasizing the critical role of surface texturing and coating strategies in promoting implant longevity and integration within the biomechanical environment of the human oral cavity.